Enhancing Hospitality Competitiveness through Facility and Price Strategy A Case Study of The Arista Hotel Palembang - Dwi Putri Marisa; Ummasyaroh Ummasyaroh; Sari Lestari Zainal Ridho (International Journal of Advanced Research in Social Studies, 2022)
The growth of the tourism industry in Palembang has contributed to the increasing importance of the hospitality sector, particularly star-rated hotels. However, recent data show a decline in hotel occupancy rates, including at The Arista Hotel Palembang, suggesting a potential gap between service offerings and customer expectations. This study aims to examine the influence of facilities and price on customers’ stay decisions at The Arista Hotel Palembang. A quantitative approach was used, involving a structured survey distributed to 120 guests who had stayed at the hotel in the past year. The data were analyzed using multiple linear regression. The findings reveal that both facilities and price have a significant and positive effect on stay decisions. Facilities emerged as the stronger predictor, highlighting the importance of service quality and physical comfort in shaping guest preferences. Price was also found to play a key role, particularly in terms of perceived fairness and value. These results contribute to the existing literature by providing context-specific evidence from a premium hotel in an emerging urban destination. The findings offer practical insights for hotel managers and local government in formulating strategic improvements to increase occupancy rates and enhance the competitiveness of the hospitality sector.